CONSTRUINDO O INÍCIO DA DOCÊNCIA EM DISTINTOS SEGMENTOS DE ENSINO - Marcela Marques Umbellino; Klinger Teodoro Ciríaco (Universidade do Oeste Paulista, 2016)
The purpose of this paper is to present data from an investigation linked to the actions of the Group of Studies and Research on the Start of Teaching and the Teaching of Mathematics (GEPIDEM/CNPq) associated with the Federal University of Mato Grosso do Sul - UFMS, Campus de Naviraí which focused on identifying the challenges faced by teachers starting their career in different levels of schooling. For such, data was collected from written and oral accounts by four teachers from the public education network who were beginning to teach in Child Education, Fundamental Education, Senior High-School, and Higher Education. Fieldwork was based on information obtained by means of reflexive diaries of teachers, as well as on semi-structures interviews in which we were looking for a better understanding of the wishes and difficulties during their transition to teaching. Thus, the analysis of data allowed to identify that the first experiences in the pedagogical work are full of intense learning and personal conflicts, as well as the institutional support that turns out to be essential in their professional development.